PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN BARANG KONSUMSI YANG TERDAFTAR DI BEI TAHUN 2015-2017 - Niken Ayu Wulandari; Tegoeh Hari Abrianto; Edi Santoso (ISOQUANT : Jurnal Ekonomi, Manajemen dan Akuntansi, 2019)
This research to analyze and evaluate intellectual capital on financial performance obtained by return on equity, asset turnover and growth in revenue. The population in this study are consumer goods companies listed on the Stock Exchange in 2015-2017. The research sample was received by 21 companies obtained by using purposive sampling technique. The analytical method used is simple linear regression analysis with the SPSS version 20 application and uses the VAICTM method to measure intellectual capital. The results of this study indicate that intellectual capital has a significant effect on financial performance generated by return on equity, but intellectual capital does not have a significant effect on financial performance required by asset turnover and growth in revenue.